装配腋撑式顶底角钢梁柱连接钢框架 (2024)
本发明公开了一种装配腋撑式顶底角钢梁柱连接钢框架，包括钢梁和与钢梁垂直设置的两个钢柱，两个钢柱分别与钢梁的两端通过顶底角钢固定连接；在靠近钢梁和两个钢柱的连接处均设置有腋撑，每个腋撑均包括斜支撑和固定设置在斜支撑两端的节点板，每个腋撑的两端通过节点板分别与钢梁和钢柱可拆卸连接，且斜支撑相对于钢梁的轴线和钢柱的轴线均倾斜设置；其中，钢框架的屈服准则为梁柱连接和腋撑先于钢梁屈服，或钢梁先于梁柱连接和腋撑屈服。相比传统的半刚性连接的加固措施，将腋撑加入半刚性钢框架中，结合了抗弯钢框架与中心支撑钢框架的优点，克服了偏心支撑钢框架的缺点。顶底角钢梁柱连接与腋撑耗能能力较好，因此整个框架耗能能力大大提升。 The invention discloses an assembled haunch support type top and bottom corner steel beam column connecting steel frame. The assembled haunch support type top and bottom corner steel beam column connecting steel frame comprises a steel beam and two steel columns perpendicular to the steel beam, wherein the two steel columns are fixedly connected with the two ends of the steel beam through top andbottom corner steel respectively; haunch supports are arranged at the positions close to the joints of the steel beam and the two steel columns, each haunch support comprises an inclined support and gusset plates fixedly arranged at the two ends of the inclined support, the two ends of each haunch support are detachably co